On the diversity, phylogeny and biogeography of cable bacteria - Ley, Philip; Geelhoed, Jeanine S.; Vasquez-Cardenas, Diana; Meysman, Filip J. R. (Frontiers in Microbiology, 2024)
Cable bacteria have acquired a unique metabolism, which induces long-distance electron transport along their centimeter-long multicellular filaments. At present, cable bacteria are thought to form a monophyletic clade with two described genera. However, their diversity has not been systematically investigated. To investigate the phylogenetic relationships within the cable bacteria clade, 16S rRNA gene sequences were compiled from literature and public databases (SILVA 138 SSU and NCBI GenBank). These were complemented with novel sequences obtained from natural sediment enrichments across a wide range of salinities (2–34). To enable taxonomic resolution at the species level, we designed a procedure to attain full-length 16S rRNA gene sequences from individual cable bacterium filaments using an optimized nested PCR protocol and Sanger sequencing. The final database contained 1,876 long 16S rRNA gene sequences (≥800 bp) originating from 92 aquatic locations, ranging from polar to tropical regions and from intertidal to deep sea sediments. The resulting phylogenetic tree reveals 90 potential species-level clades (based on a delineation value of 98.7% 16S rRNA gene sequence identity) that reside within six genus-level clusters. Hence, the diversity of cable bacteria appears to be substantially larger than the two genera and 13 species that have been officially named up to now. Particularly brackish environments with strong salinity fluctuations, as well as sediments with low free sulfide concentrations and deep sea sediments harbor a large pool of novel and undescribed cable bacteria taxa.